2005
DOI: 10.1007/s11010-005-7142-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Premna tomentosa extract (L. verbanacae) on acetaminophen-induced mitochondrial dysfunction in rats

Abstract: Allurement of herbs as health beneficial foods (physiologically functional foods) and as a source material for the development of new drugs, has led to greater furtherance in the study of herbal medicines during recent years. Plant extracts are being utilized to treat a wide variety of diseases like hepatotoxicity. Premna tomentosa is one such medicinal plant used widely in Indian ayurvedic medicine for the treatment of liver disorders. This study appraised the effectiveness of P. tomentosa leaf extract in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The mitochondrial alterations associated to PCM‐induced liver toxicity include decrease in mitochondrial oxygen consumption, ATP synthesis, mitochondrial membrane potential, and activity of mitochondrial complexes I (NADH dehydrogenase), II (succinate dehydrogenase) and IV (cytochrome c oxidase) . PCM inhibits complex II .…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial alterations associated to PCM‐induced liver toxicity include decrease in mitochondrial oxygen consumption, ATP synthesis, mitochondrial membrane potential, and activity of mitochondrial complexes I (NADH dehydrogenase), II (succinate dehydrogenase) and IV (cytochrome c oxidase) . PCM inhibits complex II .…”
Section: Introductionmentioning
confidence: 99%
“…According to literature, hepatic treatment investigations were conducted on other Premna species, including the study of hepatoprotection of alcoholic Premna esculenta, Premna corymbosa, Premna serratifolia, and Premna tomentosa leave extracts after liver induction with CCl 4 . These studies showed significant hepatoprotection by decreasing the activity of serum enzymes, bilirubin, and lipid peroxidation [40][41][42][43]. Moreover, the hepatoprotective role of the ethanol Premna integrifolia leave extract on the aflatoxin B 1 -induced toxicity was studied in mice; the study showed the protective effect of Premna integrifolia through the restoration of altered hematological indices and liver marker enzymes [44].…”
Section: Discussionmentioning
confidence: 96%
“…Several studies showed that, some of the components of certain species of citrus fruit as Bergamot orange (BO), limonene and alpha-pinene, were shown to have hepatoprotective effects (44,45,46). Therefore it is likely that BO has hepatoprotective effect.…”
Section: Discussionmentioning
confidence: 99%